Human cytomegalovirus immediate-early gene 2 expression leads to JCV replication in nonpermissive cells via transcriptional activation of JCV T antigen - Wegner, Michael; et al. (Virology, 2000)
Human papovavirus JCV is the causative agent of the demyelinating brain disease progressive multifocal leukoencephalopathy (PML) that typically develops as a complication of impaired immunocompetence. JCV displays a strong tropism for glial cells which is correlated by glial-specific transcriptional regulation of viral gene expression. In a previous report HCMV was shown to overcome the restricted cell specificity of JCV by inducing DNA replication of a PML-derived JCV strain in human fibroblasts which are nonpermissive for the replication of JCV alone. Here we show that productive JCV replication is induced by HCMV in human glioblastoma cells. Both in fibroblasts and in glioblastoma cells, the HCMV immediate-early transactivator 2 (IE2) is sufficient to mediate JCV replication. Furthermore, IE2 induces DNA replication of several structurally different brain- or kidney-derived JCV variants. IE2-induced JCV DNA replication is accompanied by the induction of JCV T antigen expression due to stimulation of the JCV early promoter. Our results indicate that stimulation of JCV early gene expression by HCMV-IE2 is sufficient to overcome the restricted cell specificity of JCV. (C) 2000 Academic Press.
UnivIS-Import:2015-03-05:Pub.2000.med.IB.LPCIPDBI.humanc